Arbeit im Nationalsozialismus - Buggeln, Marc 1971-; Wildt, Michael 1954-; Internationales Geisteswissenschaftliches Kolleg Arbeit und Lebenslauf in Globalgeschichtlicher Perspektive (De Gruyter Oldenbourg, 2014)
Work was a core concept in National Socialism. In pre-war concentration camps, it was a tool for converting prisoners into Volksgenossen, or members of the national community. And during the war, forced labor was crucial to armaments production. "Ability to work" meant life or death for Jews, POWs, and others. The essays in this volume explore the multiple meanings of work as a social, political, and cultural practice in National Socialism.